RRI Sumenep's Strategy in Facing the Era of Media Convergence - Ahmad Zulfikar Ali; Nur Azizah (Penerbit Hellow Pustaka, 2025)
Changes in communication technology that occur continuously and develop rapidly cause convetional media to converge and create new media channels or platforms that are more diverse. These changes also eencourage conventional media to transform to adapt to new technological changes. For this reason, this research discusses the strategies implemented by the Public Broadcasting Corporation of Radio Republik Indonesia (LPP RRI) Sumenep in facing challenges in the era of media convergence as well as its supporting and inhibiting factors. With Henry Jenkins’ media convergence theory and qualitative descriptive method, data were obtained through observation, interviews and documentation. The result revealed that RRI Sumenep’s strategy in facing the era of media convergence includes mapping and collecting competent human resources, then creating content that can be watched through RRI Sumenep’s own Youtube, its own page on the rri.co.id website, and social media accounts that each program belongs to RRI Sumenep itself. In conclusion, the strategy applied by RRI Sumenep is effective in increasing audience reach and streghthening the existence of institutions in the digital realm.